The Tacticality of Working Capital - N. Emongor, Elizabeth (International Journal of Scientific Research and Management (IJSRM), 2023)
In today's dynamic and competitive business landscape, the effective management of working capital has emerged as a critical factor for the success and sustainability of organizations. Literature review has shown that working capital management can be an effective survival tool in a tough macroeconomic environment where businesses can enhance their ability to meet short-term obligations, improve cash flow, and ultimately achieve long-term success. As businesses strive to maintain financial stability and optimize operational efficiency, tactical working capital management has taken center stage. This research sheds light on the importance of working capital management and how it affects companies. The study goes on to demonstrate that working capital management may influence the performance of a firm and therefore its strategic management can enhance business sustainability.